Evaluation of urban water cycle health status based on DPSIRM framework and AHP-FCE-Cloud model - Jiageng Hu; Fuqiang Wang; Peiheng Liu; Subing Lü; Cheng Lü; Furong Yu (Ecological Indicators)
As urbanization accelerates, the trend of “dual evolution” in the water cycle has intensified, leading to numerous water resource issues and posing significant challenges to urban water cycle health. Accurately evaluating and analyzing urban water cycle health is crucial for addressing these challenges. However, time lags in policy implementation and extreme weather events from climate change negatively impact evaluation accuracy, complicating the research. This study employs the Driving force-Pressure-State-Impact-Response-Management (DPSIRM) framework, using key policy implementation milestones as benchmarks to divide the timeline into three evaluation phases, thereby optimizing the urban water cycle health evaluation system. By integrating the Cloud model with the Analytic Hierarchy Process-Fuzzy Comprehensive Evaluation (AHP-FCE) model, an improved AHP-FCE-Cloud model is constructed. Zhengzhou is used as a case study to evaluate the health status of the water cycle across three periods: 2010–2013, 2014–2017, and 2018–2021, comparing results with the traditional AHP-FCE model while exploring the obstacles affecting water cycle health. The results indicate a continuous improvement in Zhengzhou’s water cycle health, rising from an unhealthy level in 2010–2013 to a sub-healthy level in 2014–2021. The pressure subsystem is the primary constraint, with its obstacle strength weakening over time (from 0.42 to 0.28), while the impact of the driving force subsystem becomes more pronounced (from 0.03 to 0.37). The AHP-FCE-Cloud model provides a more scientific and effective method for evaluating urban water cycle health and offers significant reference value for similar research. Furthermore, the analysis of obstacles provides theoretical support for promoting sustainable urban development.